Cell Death Triggers Induce MLKL Cleavage in Multiple Myeloma Cells, Which may Promote Cell Death - Chen, Jing; Wang, Shiyu; Blokhuis, Bart; Ruijtenbeek, Rob; Garssen, Johan; Redegeld, Frank (Frontiers in Oncology, 2022)
Necroptosis is a type of caspase-independent programmed cell death that has been implicated in cancer development. Activation of the canonical necroptotic pathway is often characterized with successive signaling events as the phosphorylation of mixed lineage kinase domain-like (MLKL) by receptor-interacting protein kinase-3 (RIPK3), followed by MLKL oligomerization and plasma membrane rupture. Here, we demonstrate that omega-3 polyunsaturated fatty acids DHA/EPA and the proteasome inhibitor bortezomib induce necroptosis in human multiple myeloma (MM) cells in a RIPK3 independent manner. In addition, it seemed to be that phosphorylation of MLKL was not essential for necroptosis induction in MM cells. We show that treatment of MM cells with these cytotoxic compounds induced cleavage of MLKL into a 35 kDa protein. Furthermore, proteolytic cleavage of MLKL was triggered by activated caspase-3/8/10, and mutation of Asp140Ala in MLKL blocked this cleavage. The pan-caspase inhibitor ZVAD-FMK efficiently prevented DHA/EPA and bortezomib induced cell death. In addition, nuclear translocation of total MLKL and the C-terminus were detected in treated MM cells. Collectively, this present study suggests that caspase-mediated necroptosis may occur under (patho)physiological conditions, delineating a novel regulatory mechanism of necroptosis in RIPK3-deficient cancer cells.